Effect of cellulose nanocrystals content and pH on swelling behaviour of gelatin based hydrogel - Ooi, Shok Yin; Ishak Ahmad,; Mohd Cairul Iqbal Mohd Amin, (Universiti Kebangsaan Malaysia, 2015)
In this research, a novel method was performed to obtain hydrogel with superior thermal stability by incorporation of cellulose nanocrystals (CNC) into gelatin based hydrogel. Glutaraldehyde was used as cross-linker due to its high chemical reactivity towards NH2 group on gelatin. Different ratio of gelatin/CNC hydrogel was produced in order to study the effects of CNC towards the swelling behaviour and thermal stability of gelatin based hydrogel. The obtained hydrogel was subjected to Fourier transform infrared (FTIR) to verify that gelatin had been cross-linked, swelling test with different pH for swelling behaviour and thermogravimetric analysis (TGA) for thermal stability. The presence of C=N stretching group in the FTIR spectrum for gelatin/CNC hydrogel indicated that the cross-linking reaction between gelatin monomer had been successfully carried out. The hydrogel showed impressive pH sensitivity and maximum swelling was obtained at pH3. The TGA results clearly showed that the incorporation of CNC into gelatin was able to produce hydrogel with higher thermal stability compare to neat gelatin.